Ugly Truths About Runaway College Tuition. - Vedder, Richard (American Enterprise, 2004)
Thanks to American universities' unbusinesslike nature, inefficiencies, and total lack of accountability for the resources entrusted to them, college tuition fees are higher than ever in fall 2004. Ten major sources of today's soaring tuition costs are identified and outlined.